PREPARATION AND CHARACTERIZATION OF KETOPROFEN NANOSUSPENSION FOR SOLUBILITY AND DISSOLUTION VELOCITY ENHANCEMENT - MOHAMED A AMIN; SHAABAN K. OSMAN; USAMA F. ALY (International Journal of Pharma and Bio Sciences, 2013)
Nanosuspension technology has been developed as a promising candidate for efficient delivery of hydrophobic drugs. It could maintain the required crystalline state of the drug with reduced particle size, leading to an increased reporting on dissolution rate and therefore improved bioavailability. In this paper, we report on the preparation of ketoprofen (KTF) nanosuspension by high-pressure homogenization (HPH). The aim is to obtain a stable nanosuspension with an increased drug saturation solubility and dissolution velocity. The morphology and particle size distribution of the modified nanosuspensions were characterized by the means of several analyses that included: photon correlation spectroscopy (PCS), polarized light microscopy (PLM), scanning electron microscopy, differential scanning calorimetry (DSC), and powder X-ray diffractometry (XRD). The obtained results revealed that HPH can be employed to produce aqueous drug nanosuspensions with fine solubility and dissolution properties, which render the produced particles stable up to one month. In addition, the prepared nanosuspensions possessed a high drug-loading efficiency (10%). The recoded zeta potential values (≈ - 27 mV) indicated that the prepared nanosuspensions possess a higher degree of long-term stability. PCS data showed narrow size distribution with average size 322.7 nm. Morphologically, as indicated from results, the produced nanosuspensions have a homogenous distribution even after redispersion, indicating the stability of the product.